Pyramidal Lobe of the Thyroid Gland: Surgical Anatomy in Patients Undergoing Total Thyroidectomy. (7th July 2015) - Gurleyik, Emin; Gurleyik, Gunay; Dogan, Sami; Cobek, Utku; Cetin, Fuat; Onsal, Ufuk
Abstract : Background . Anatomic variations, the presence of the pyramidal lobe (PL), may impact completeness of thyroidectomy and effect of surgical treatment. Method . This study included 166 patients who underwent total thyroidectomy. The anterior cervical region between the thyroid isthmus and the hyoid bone was dissected during thyroid surgery. The incidence, size, and anatomical features of the PL were established in these patients. Results . The incidence of PL was 65.7%. No gender difference was found for PL incidence. The base of the PL was located at the isthmus in 52.3%, the left lobe in 29.4%, and the right lobe in 18.3% of patients. The mean length of the PL was 22.7 (range, 5–59) mm. The PL was longer than 30 mm in 23% of patients. One-third of the patients with short PL were men whereas women accounted for 80% of patients with long PL. Conclusions . The high incidence indicates that the PL is a common part of the thyroid. The PL generally originates from the isthmus near midline and is of variable length, extending from the isthmus up to the hyoid bone. Considering that the PL is a common structure, the prelaryngeal region should be dissected to achieve the completeness of thyroidectomy.